THE INTERPLAY BETWEEN LEARNING MEDIA, MOTIVATION AND LEARNING OUTCOMES: INSIGHTS FROM INDONESIAN EFL CONTEXT - Iswadi Iswadi (Research and Development Journal of Education, 2021)
The objectives of the study are to explore the impact of English comic learning media towards English’s learning outcomes, the  impact of   learning motivation towards English’s learning outcomes, and the  interaction effect between  English comic learning media and learning motivation towards English’s learning outcomes. The method of research is experimental with 2x2 factorial design. Data collection techniques are multiple choice and questionnaires. Population of the study are 175 students. Sample of the study are 60 students. Random sampling are  used for gaining sample. The researcher used SPSS 22.0 version to analyze data. The  conclusions of  this study are: (1) There is a significant  impact of English comic learning media towards English’s learning outcomes because significant value is 0.000 < 0.05.(2) There is a significant impact of learning motivation towards English’s learning outcomes because significant value is 0.000 < 0.05. (3) There is a significant  interaction impact between  English comic learning media and learning motivation towards English’s learning outcomes because significant value is 0.004 < 0.05.